Healthcare industry challenges and potential opportunities in the Uae. A review paper - Rafeea, Salama Jamal; Al-Shami, Samer Ali Hussein; Alkaabi, Khaled Mohammed; Abdul Rashid, Nurulizwa (Allied Business Academies, 2021)
The development of the health sector is one of the most important priorities of policy-makers in the United Arab Emirates (UAE), as it has a direct impact on the citizens’ well-being and productivity. However, it is fraught with challenges due to the overlapping and complexity of operations that require capital and high technology, which may exceed the state's capabilities. Despite the theoretical enrichment about the development of the health system, there is a contradiction in the methods on the one hand, and a discrepancy in the studies, especially in focusing on the developed and western countries on the other hand. Therefore, this paper aims to review and discuss the challenges and opportunities of the health system in developing countries, especially the UAE by through the interaction between leadership and corporate entrepreneurship, which is the key driver for innovation and healthcare sustainability.